PCR-RAFT: rapid high throughput oxygen tolerant RAFT polymer synthesis in a biology laboratory. Issue 6 (8th January 2020) - Gurnani, Pratik; Floyd, Thomas; Tanaka, Joji; Stubbs, Christopher; Lester, Daniel; Sanchez-Cano, Carlos; Perrier, Sébastien
Abstract : We performed high-throughput oxygen tolerant ultra-fast RAFT polymerisation producing complex polymer libraries utilising PCR thermocyclers. This now enables the preparation of these libraries in under 5 min without chemistry equipment. Abstract : Some of the main applications for synthetic polymers are found within the medical field (drug delivery, diagnostics, medical imaging). However, preparation of these macromolecules has been limited to those with access to chemistry facilities, potentially delaying biological evaluation. In this work, we aim to address this issue by utilising equipment typically found within a biological lab to establish a protocol for the preparation of well-defined macromolecules via RAFT polymerisation. By exploiting thermocycler technology, libraries of homopolymers, block- and statistical-copolymers were prepared in under 5 minutes per heating cycle using acrylamide monomers with ultrafast RAFT polymerisation. All the polymers prepared had excellent molar mass control and could be generated in under 15 min.